PENGGUNAAN MEDIA DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PERUBAHAN LINGKUNGAN FISIK TERHADAP DARATAN - MULZA - ROIS; Randi Eka Putra; Mardaini - (Jurnal Muara Pendidikan, 2018)
Material changes in the physical environment are one of the science learning materials that are difficult for students to understand. For this reason, an efficient learning media is needed and serves to visualize the process of changing the physical environment to the land. Model media is one of the media that can be used to improve students' understanding of learning material changes in the physical environment to the land. This has been proven by researchers in a PTK, in class IV SD Negeri 27 Sawahan Dalam Timur District. The results of this study prove that the use of media models can improve student learning outcomes. Research cycle I shows that the average acquisition of student learning outcomes is 7.3, while in cycle II the average value of student learning outcomes is 8.6. From the final results of the learning process, the value obtained by students has increased. Based on these results it can be concluded that this study shows that the use of media models can improve student learning outcomes in learning changes in the physical environment to land in class IV SD Negeri 27 Sawahan Dalam, Padang Timur District was well achieved.